Design of New Antenna in the Form of Dollar-symbole for WLAN Technology. (2016) - Hati, Khalid; Sabbar, Nisrin; Hajjaji, Abdellah El; Asselman, Hassan
Abstract: Nowadays, several interesting patch antenna structure is proposed. In this paper, we are proposing a new rectangular structure in the form of a dollar-symbole, fed by a microstrip line is made with FR4 substrate, a thickness of 1.6 mm, and a relative permittivity of 4.4. The ground plane on the antenna is printed, while contain two slots. The resulting antenna has been found to possess a compact size of 30 mm × 30 mm, and suitable for wireless local area network (WLAN). Two resonant frequencies are obtained by the proposed antenna. The low-band resonant frequency is located at about 2.4 GHz, with -10 dB impedance bandwidth from about 1.9 GHz to 3 GH, and the high-band resonant frequency is located at about 8.8 GHz, with -10 dB impedance bandwidth from about 7.6 GHz to 10 GHz. In the first part, a comparison study of a patch antenna with slots and without slots is proposed; in the second part, the study of antenna parameters which affect dimensions is presented.